2016
DOI: 10.1007/s11095-016-1929-x
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Absorption of Dry-Powder Intranasal Oxytocin

Abstract: The PK and stability data suggests that IN administration of oxytocin formulated in the μco™ carrier may represent a viable option for rapid systemic absorption in humans and a product compatible with resource-scarce regions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…Thus, its activation should partially account for the increased plasma ACTH and the subsequently increased plasma corticosterone levels following IAO. In addition, because lactating rats exhibited a high degree of CRH and VP colocalization in parvocellular PVN neurons, hypothalamic projections, and median eminence terminals compared to virgins, it is possible for a simultaneous increase in VP and CRH in the PVN (Milewski et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, its activation should partially account for the increased plasma ACTH and the subsequently increased plasma corticosterone levels following IAO. In addition, because lactating rats exhibited a high degree of CRH and VP colocalization in parvocellular PVN neurons, hypothalamic projections, and median eminence terminals compared to virgins, it is possible for a simultaneous increase in VP and CRH in the PVN (Milewski et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Both these demonstrate good safety profile, fast absorption and rapid onset of action. Intranasal powder formulations of different drugs such as oxytocin and dihydroergotamine are also under development [ 79 , 80 ]. It has been suggested that powder formulation is more likely to trigger local irritation than its equivalent liquid formulation, a particular consideration in chronic use.…”
Section: Intranasal Deliverymentioning
confidence: 99%
“…Moreover, it is now under clinical evaluation for delivery of fluticasone propionate for the treatment of chronic rhinosinusitis (Djupesland, 2013;Hansen et al, 2010). Pharmacokinetic studies in monkeys have revealed good in vivo absorption rate of oxytocin from the dry powder of the active with co ® carrier, rapid onset of the effect and reasonable nasal bioavailability (12% of intramuscular bioavailability) (Milewski et al, 2016).…”
Section: Nasal Powder Insufflatorsmentioning
confidence: 99%